EVALUASI ANGGARAN PENDAPATAN BELANJA BARANG DAN PEMELIHARAAN INVENTARIS KANTOR PADA BADAN PENGELOLAAN KEUANGAN DAN KEKAYAAN DAERAH KABUPATEN SLEMAN - , Melkias Namora; , Eko Suwardi, Dr., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims at identifying: 1) trend of budget for goods and services office equipment in the financial district, Sleman Board 2) budget in comparison with requirements and maintenance of equipment in the financial district, Sleman Board 3) conformity of the maintenance budget for the Office products and office equipment in the financial District of Sleman compared to existing laws and regulations. The results of this research analysis found: 1) Expenditures for goods and services during 2006, precisely a decrease in fiscal year 2006, ie there is a difference of about Rp.400 hundred million. The amount budgeted development expenditure in 2006 amounted to Rp. 4,881,629,788.94 while the realization of only Rp. 4,752,240,523.68, while the realization of goods and services expenditures in 2005 amounted to Rp.5.163.987.456, 00. This indicates that there are development programs that can not be realized for any reason. 2) Budget for 2005-2009 has been carried out in accordance with applicable legislation and in accordance with the Strategic Plan document and I am budget that has developed between the legislative team with the executive team. Account that appear in the budget for 2005-2009 budget already includes programs intended priority in the Strategic Plan and Budget in 2005 Sleman. Budgets were also reports in accordance with the laws and regulations, such as SE Mendagri (Minister of Domestic Affairs) 903/2429/S3 in 2005 and in accordance with Permendagri number 13 in 2006. Because budgeting in 2005 was in accordance with the laws and regulations, strategic planning and budgeting, I concluded that the budget is to be effective.